The Relationship between functional movement quality and speed, agility, and jump performance in elite female youth football players - Alexe, D. I.; Cauševic, D.; Covic, N.; Rani, B.; Tohanean, D. I.; Abazovic, E.; Setiawan, E.; Alexe, C. I. (Sports, 2024)
The association between movement screening and physical fitness testing in athletes is conflicting, and therefore, this study aimed to examine the relationship between Functional Movement Screen (FMS) performance and physical performance in elite female youth football players. Twenty-two players from the national U16 team of Bosnia and Herzegovina underwent FMS and physical performance tests, including speed, agility, and jump assessments. Jump and speed performance score correlated well with ASLR, while the overall FMS score was not associated with any of the performance variables. These findings suggest that while certain movement patterns may impact athletic performance, the relationship between movement screening and physical performance is delicate. Coaches and practitioners should consider individual variations and sport-specific demands when interpreting FMS results in order to optimize and maximize athlete performance and reduce injury risks.